Analysis of Current Ratio and Debt to Equity Ratio on Return On Assets with Company Size as a Moderating Variable - Mardiyani, Mardiyani; Maiyaliza, Maiyaliza; Hidayat, Rahmat Rian; Pramudya, Muhammad Dwika (LPPM of NAROTAMA UNIVERSITY, 2025)
Objective: This study’s aim is to do an analysis on the effect of current ratio along with debt to equity ratio on return on assets in the property and real estate sub-sector that is on Indonesia Stock Exchange’s (IDX) list during 2020-2023, with the moderating variable being company size. Design/Methodology/Approach: Quantitative research methods were implemented for this study, with a causal associative approach. Moderated Regression Analysis (MRA) was applied as the technique for data analysis, with Eviews statistical software utilized. Findings: The findings revealed that current ratio as well as debt to equity ratio impact return on assets significantly. This means that an increased liquidity, along with the proportion of debt can reduce the efficiency and profitability of the company. Company size strengthens the effect by functioning as a moderating variable. Research Implications: This research only focuses on the real estate and property sub-sector that is on IDX’s list during 2020-2023. Therefore, this study’s results may not be generalizable to different sectors or periods. Practical Implications: Investors and company management can use this study’s results as a basis for financial decision-making, particularly in managing liquidity as well as leverage for increased profitability. Originality/Value: New insights are provided by this study into company size’s role as the moderating variable for the relationship between leverage, liquidity, along with profitability, especially in the real estate and property sector. Types of Papers: Research paper.